STUDI PEMBUATAN TEMPE DARI BIJI KARET - Bakhrin ,; Rahmi Zulhida; Deni Seno (AGRIUM: Jurnal Ilmu Pertanian, 2013)
This study aimed to investigate the effect of different concentrations of yeast in making tempeh from seed karet.Rancangan completely randomized (CRD) was used with two (2) yeast replication factor I concentrations (K) comprises 4 levels, yaituK1 = 0.2%, K2 = 0.4%, 0.6% = K3, and K4 = 0.8%. factor of 2 long fermentation (L) comprises 4 levels ie L1 = 12 hours = 24 hours L2, L3 = 36jam, L4 = 48 hours. The concentration of yeast members very real effect on carbohydrate carbohydrates where K1 is the highest at 8.850% was the highest carbohydrate fermentation contained in L1 is 8.360%. Keywords: tempeh, beans, yeast, fermentation